If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(k-5)-8=-8(k-7)
We move all terms to the left:
4(k-5)-8-(-8(k-7))=0
We multiply parentheses
4k-(-8(k-7))-20-8=0
We calculate terms in parentheses: -(-8(k-7)), so:We add all the numbers together, and all the variables
-8(k-7)
We multiply parentheses
-8k+56
Back to the equation:
-(-8k+56)
4k-(-8k+56)-28=0
We get rid of parentheses
4k+8k-56-28=0
We add all the numbers together, and all the variables
12k-84=0
We move all terms containing k to the left, all other terms to the right
12k=84
k=84/12
k=7
| 5.50h+20=6.50h+15 | | N=3n+16 | | 3(a+8)+1=-3(3-7a)-2 | | 57-3=2y+9 | | 8a+4=6a+4 | | 3(2-k)=-3k=2 | | x/4-19=20 | | -3(6+3x)=-(6x+3) | | 6+8x=11x | | y/5+10=11 | | -3x+10=-38 | | 6(m-4)+5=-5(6-m) | | -2x+8(x+7)=7+5(1-x) | | -8-(6-8m)=2(m-1) | | 51=5(3a+6)-8 | | 7(4-4x)=-8(1+3x) | | 30.25x=60 | | 17=3-2(2f-1) | | 5x+3–3x+2=35 | | -(7x-1)+14=21 | | 8+w/2=11 | | 0.05x=37.25 | | 2m=78 | | 13-3k=7 | | 26+4.25.x=60 | | -3(-6b-4)=6(4b+6) | | -6u-36=−42 | | -4(m-1)=-8 | | -6u-36= | | 16/4=v | | 9.43=k−9.64 | | 2(4x+2)+x=9x-4 |